Adverse events following immunization (AEFI) reports of extended program immunization (EPI) in Indonesia during 1998-2002 - Nastiti Kaswandani; Sri Rezeki Hadinegoro; Rulina Suradi (Indonesian Pediatric Society, 2004)
Background The incidence of adverse events following immuni-zation (AEFI) increased in correlation with the number of vaccinedoses. Meanwhile AEFI reports should be managed properly tomaintain the compliance and immunization coverage.Objectives The aims of this study were to investigate the inci-dence and profile of AEFI, its onset, severity, classification, andoutcome.Methods This study was a passive surveillance of AEFI reportsreceived by the National Committee on AEFI, Ministry of Health ofIndonesia, during 1998 to 2002.Results Two hundreds and four AEFI cases were reported; 4 casesas zero reports, 182 cases as individual reports, and 18 clusterreports. The AEFI incidence was 0.44 per 1 million doses of vac-cines. Vaccine reaction rate was 1 per 2.3 million vaccine doses.The most common vaccines reported as the causes of AEFI wereDTP, Polio, and TT. Among 182 reported cases, local or mild AEFIreactions were observed in 45, moderate in 49, and severe in 88.Based on WHO field classification, this study reported that 84 casesbelonged to coincidence, 72 to vaccine reactions, 13 to program-matic errors, 7 to injection reactions, and 6 to unclassified reac-tions. Forty-seven patients died, 12 had some sequelae, and 123completely recovered. Meanwhile, among the death cases, 70%occurred coincidently, 17% due to vaccine reactions, and 6 wereunclassified.Conclusions The incidence of AEFI in the extended program im-munization (EPI) in Indonesia during the period of 1998-2002 were182 cases, thus vaccine reaction rate was 1 per 2.3 million vac-cine doses. The most common vaccine which caused AEFI wasDTP. Most AEFI with severe symptoms happened in 4-24 hoursafter immunization.